Motivation, Learning Activity, and Learning Outcomes of Grade V Elementary School - Yogi Alfian (INTERNATIONAL JOURNAL OF EDUCATIONAL REVIEW, 2019)
The purpose of this study is to determine the effect of ice breaking on learning motivation, active learning and learning outcomes of fifth-grade elementary students, Bengkulu City. Non-Equivalent Control Group Design in the form of the quasi-experimental method was used in this study. The type of research is quantitative descriptive. The population were the public elementary students in Bengkulu City, while the sample of this study were two classes, those were VA and V B. Data collection techniques in this study were questionnaires and tests. Based on the description of the results of the research and discussion, it can be concluded that (1). There is an influence of ice breaking on the learning motivation of fifth-grade students of public elementary school 56 Bengkulu City. This is shown in the t-test that the value of t-test of 5.00> t table value at a significant level of 5% is 2.01 (2). There is an influence of ice breaking on the learning activeness of fifth-grade students of public elementary school 56 Bengkulu City. This is shown in the t-test that the value of t-test is 5.04> t table value at the 5% significance level of 2.01. (3). There is a significant effect of ice breaking on student learning outcomes on cognitive aspects of fifth-grade students of public elementary school 56 Bengkulu City. This is indicated by the calculation of the t-test that the value of t testis 2.71> the value of t table at a significant level of 5% of 2.03.